Abstract Braumann+Filipe ECMTB 2008 - Braumann, Carlos A. (2009)
Oral communication at the international conference ECMTB 2008 (European Conference on Mathematical and Theoretical Biology, Edimburgh, U.K., June-July 2008). web page: http://www.maths.dundee.ac.uk/ecmtb08/ Study and parameter estimation for one and several trajectories (including bootstrap methods) of stochastic differential equation models for the growth of individual animals in randomly fluctuating environments.